Plan de marketing para el micro mercado víveres Aracely de la ciudad de Shushufindi, del cantón Shushufindi, provincia de Sucumbíos, para el año 2016 - Ruiz Lucas, Liliana Margarita (2017)
The general objective proposed and achieved in the present research is to elaborate a proposal of a marketing plan for the Micro Market "Víveres Aracely" of the canton Shushufindi, in order to contribute strategies and solutions that help the optimization of resources In order to meet the general and specific objectives proposed, it was necessary to use a methodology, which was based on the application of several research methods such as the scientific, inductive and deductive method; In addition, techniques such as the interview and survey that contributed to the development of the work were used. For the collection of information, the following procedure is performed: First, to carry out the internal analysis of the Micro Market, for which an interview was applied to the Owner Manager; 354 surveys were applied to the company's clients and 5 employee surveys. This made it possible to identify among the main strengths (product quality satisfies customers, good work environment) and major weaknesses (limited job training and lack of a corporate image). In the second procedure, the analysis of the external factors of the Micro Market was carried out. Therefore, an analysis of the Political, Economic, Social and Technological Factors (PEST) was carried out. (Market growth, alliances with public and private institutions to deliver products) and the main threats (tax reforms, entry of new competitors) of the Micro Market. Based on these premises, the SWOT analysis was carried out, the MEFE and MEFI External Factor Evaluations matrices, corresponding to the situational diagnosis and the results of the interpretations and connotations were obtained strategic objectives described below: From the results obtained in the present investigative work, it is concluded that, the Micro Market Lives Aracely internally has strengths that overcome the weaknesses, since it obtains a weighted value of 3.19; Which is higher than the 2.50 standard. As for the external, the opportunities outweigh the threats, since they have a weighted value of 2.97, higher than the reference standard. Based on the diagnosis made, the marketing plan was proposed, which is intended to achieve, increase in sales, differentiation compared to competition, recognition in the market and customer loyalty. For the implementation of the marketing plan, a budget of USD 10,500 is required.